Recent advances in the utilization of copper sulfide compounds for electrochemical CO2 reduction - Yingkang Chen; Kejun Chen; Junwei Fu; Akira Yamaguchi; Hongmei Li; Hao Pan; Junhua Hu; Masahiro Miyauchi; Min Liu (Nano Materials Science, 2020)
Converting carbon dioxide (CO2) into value-added chemicals by CO2 reduction has been considered as a potential way to solve the current energy crisis and environmental problem. Among the methods of CO2 reduction, the electrochemical method has been widely used due to its mild reaction condition and high reaction efficiency. In the electrochemical reduction system, the CO2 electrocatalyst is the most important part. Although many CO2 electrocatalysts have been developed, efficient catalysts with high activity, selectivity and stability are still lacking. Copper sulfide compound, as a low-toxicity and emerging material, has broad prospects in the field of CO2 reduction due to its unique structural and electrochemical properties. Much progress has been achieved with copper sulfide nanocrystalline and the field is rapidly developing. This paper summarizes the preparation, recent progress in development, and factors affecting the electrocatalytic CO2 reduction performance with copper sulfide compound as a catalyst. Prospects for future development are also outlined, with the aim of using copper sulfide compound as a highly active and stable electrocatalyst for CO2 reduction.